Existence of solutions of some quadratic integral equations - Giuseppe Anichini; Giuseppe Conti (Opuscula Mathematica, 2008)
In this paper we study the existence of continuous solutions of quadratic integral equations. The theory of quadratic integral equations has many useful applications in mathematical physics, economics, biology, as well as in describing real world problems. The main tool used in our investigations is a fixed point result for the multivalued solution's map with acyclic values.